Life Cycle Sustainability Assessment of Refuse-Derived Fuel Life Cycles in Developing Countries: A Bibliometric Systematic Literature Review - Savarani Aulia Ihsani; Yudha Prambudia; Iphov Kumala Sriwana; Ibnu Zulkarnain; Juniza Md Saad (Universitas Trisakti, 2026)
Waste management poses a critical global challenge, particularly in developing countries. Refuse-Derived Fuel (RDF) offers a promising solution, necessitating holistic sustainability evaluations through Life Cycle Sustainability Assessment (LCSA). Aim: This study aimed to conduct a systematic and bibliometric review mapping trends, analyzing methodologies, identifying barriers, and evaluating strategies concerning LCSA development in RDF life cycles within developing countries. Methodology and results: Employing a Bibliometric-Systematic Literature Review (B-SLR) using Scopus data (2011-2024) and analyzed via VOSviewer and qualitative content analysis, the study identified 22 relevant publications. Findings reveal a fluctuating yet growing publication trend with increasing citations, though international collaboration remains limited despite concentrated productivity. Methodologically, studies predominantly use LCA and LCC, with scarce S-LCA integration; key themes include environmental impacts, waste-to-energy (especially RDF in cement), and circular economy. Implementation faces significant technical, economic, social, and regulatory barriers. Proposed strategies emphasize crucial advancements in infrastructure, process optimization, stakeholder engagement, and robust regulatory frameworks. Conclusion, significance and impact study: The findings confirm that while scholarly interest in LCSA for RDF is increasing, its application is fragmented and hindered by persistent barriers. This research provides a crucial synthesis of evidence-based insights for policymakers and enriches academic understanding of LCSA in alternative waste management. Future work should prioritize developing integrated LCSA methodologies (especially for S-LCA), addressing critical data gaps, conducting holistic case studies, fostering international collaboration, and validating proposed strategies to accelerate sustainable RDF adoption and comprehensive waste management.